STRATEGI PENYIARAN RADIO TRAX FM DALAM MENARIK MINAT DENGAR (Studi Kasus pada Program Siaran Good Alternoon Show Radio 101.4 Trax FM Jakarta) - Drianita Kurnia Asniyarti (2020)
This Research is studying the strategy carried by 101.4 FM Trax Radio Jakarta, in its effort to get the interest of its listener through the new program of Trax FM called GOOD ALTERNOON SHOW. This program has an interesting strategy of broadcast by the unique concept, unique content, also the special segment that presented for the young and teenager, so it will be formed the interest of listening from the audience for listening, even being consistent to enjoy the content of the program. This research aims to know and to describe the strategy of programming the Trax FM as radio, in terms of getting the interest of listeners from the GOOD ALTERNOON SHOW program. The method that will be used in this research is the descriptive qualitative method. The collection of data will be using the in-depth interviewing and observing technic, which targeting the producer of the program, the program director, the announcer, and the listener of TRAX FM, also the data will be supported by documentation. The results of this research show that in order to get the interest of listeners, 101.4 FM Trax Radio implementing the program strategies. Those strategies are choosing the unique name for the program, choosing the right communicator (announcer) that suitable with the target (listeners), the compatibility of broadcasting concept with the interest and need of society in informative and entertaining way but not weary, the appropriateness of communication form that is interesting and having character, the diversity way of effective promotion by on-air promotion, off-air promotion, and cross-promotion, giving a priority to the interaction between listeners and the announcer of the program, and the most important thing is presenting the different segments every day, which can gather all of the listeners from all backgrounds, interests, and various group of people.